Preliminary Study: Sleep Duration and Sleep Quality in Male College Students - Elrisfa Magistarina; Zakwan Adri; Verlanda Yuca (Universitas Negeri Padang, 2021)
College students are in the period of transition from adolescence to adulthood. This transition period can bring some obstacles for them, for example, disruption in sleeping pattern. According to Tsai & Li (2004), emerging adults usually have sleep deprivation. Another recent study found that college-age teens or emerging adults do have changes in sleep patterns (Lund, Reider, Whiting, & Prichard, 2010). Those emerging adults tend to stay up late and then delay waking up-time. Based on the initial interview, many students complaint that sleep later affects their academic performance, for instance, being late to the class; daytime sleepiness; and difficulties in paying attention in the class. Thus, we would like to examine the relationship between the duration of sleep with sleep quality. The result shows that there was a significant and negative correlation between sleep duration and sleep quality, which means that the sleep quality was slightly determine by how long someone sleeps. Besides, only 5% of the respondents are not using their gadget before bed. The use of gadget affects sleep difficulties and lead to poor sleep quality. Thus, the result of this research will be used as our initial data to study further